Panorama das microfinanças: agentes, regulação e tendências - Ramon Silva Vilarins (2010)
The purpose of this study is to explore the current status of microfinance, that is, the provision of appropriate and sustainable financial services for low-income population in Brazil, its trends and the regulatory framework of the segment. In examining the microfinance regulation, the essay tries to show how current practices may in some cases inhibit the growth of microfinance in Brazil. To achieve this goal, the national and international literature on the topic of microfinance commercialization and regulation was examined. In addition, the study reviewed various recommended practices for regulation and policies adopted by other nations, in order to compare to what has been adopted in Brazil in terms of regulation for the sector. The analysis suggests that the imposition of a ceiling on interest rates for microcredit operations carried out with Interfinancial Deposits of Microcredit, the prohibition of alternative funding for microfinance institutions and the unsuitability of the current services of credit information to microcredit operations, may hinder the increase in the supply of financial services to low-income people in Brazil.